Systems design and control of a freeflying space robotic manipulator system (ATLAS) for in-orbit satellite servicing operations - Ellery, Alexander (Cranfield University, 1996)
This thesis is concerned with a freeflyer robotic spacecraft for in-orbit satellite servicing employing a dedicated attitude control system, ATLAS (Advanced TeLerobotic Actuation System). It adopts a unique control system design to alleviate the reaction coupling between the spacecraft mounting and the manipulator such that control of both the spacecraft attitude and manipulator kinematics may be effected in real-time using present-day space-rated electronics. It has been found that very few additional computations are required to compensate the coupling problem over standard terrestrial resolved motion robot control algorithms and standard spacecraft attitude control techniques. A mathematical proof of the concept is outlined. The technique is also extended for dual-arm operation. Two manipulator arms are necessary for EVA-equivalence to afford maximum flexibility. Mutual collision possibilities will be eliminated by incorporating a modified Zambesi bridge via interrupt software whereby each manipulator is restricted to operations within its own quadrant. This eases the computational burden of monitoring arm-to-arm collisions in the open chain mode with little loss of flexibility. Closed chain mode is shown to be similar to the open chain mode but with the addition of certain kinematic and force constraints. Each arm must be capable of operating independently or cooperatively, necessitating a hierarachical control architecture which is compatible with the NASREM control architecture. Given that the single arm freeflyer is the baseline of this thesis and that dual arm configurations are merely extensions of this, a simulation program of the techniques outlined has been constructed to output some of the parameters o f interest. Consideration is also given to the possible commercial impact of such a system.